The Rapidly Evolving Concept of Whole Heart Engineering - Laura Iop; Eleonora Dal Sasso; Roberta Menabò; Fabio Di Lisa; Gino Gerosa (Hindawi Limited, 2017)
Whole heart engineering represents an incredible journey with as final destination the challenging aim to solve end-stage cardiac failure with a biocompatible and living organ equivalent. Its evolution started in 2008 with rodent organs and is nowadays moving closer to clinical application thanks to scaling-up strategies to human hearts. This review will offer a comprehensive examination on the important stages to be reached for the bioengineering of the whole heart, by describing the approaches of organ decellularization, repopulation, and maturation so far applied and the novel technologies of potential interest. In addition, it will carefully address important demands that still need to be satisfied in order to move to a real clinical translation of the whole bioengineering heart concept.